A STUDY ON POST-90S EMPLOYEE’S TURNOVER INTENTION FROM THE PERSPECTIVES OF LEADER-MEMBER EXCHANGE (LMX), JOB SATISFACTION AND PERCEIVED ORGANIZATIONAL SUPPORT IN SERVICE INDUSTRY, CHINA - He, Chen (2019)
The issue of high turnover rate is becoming increasingly serious globally, which in turn lead to various problems to the organizations and society. Such alarming social fact intrigues researcher to investigate the factors that contribute to the employee's intention to leave. Moreover, post-90s generations have been formatting the major labour force in China within the next several decades. It means that the stability of post-90s employees in the workplace could benefit the entire labour market. Based on the above two issues, the researcher determines to conduct research in terms of identifying the turnover intention of post-90s employees in China. Specifically, to identify the relationship between perceived organizational support, job satisfaction and leader-member exchange and turnover intention. Besides, this researcher chooses the service industry as a targeted sector since China has gradually transferred the economic growth pattern from the manufacturing industry to the service industry. Therefore, the findings of this research would be more practical and feasible for more organizations.